PENDIDIKAN INKLUSIF DI INDONESIA: STUDI PUSTAKA ATAS PERKEMBANGAN, TANTANGAN, DAN STRATEGI IMPLEMENTASI - Debi Yanti Nahampun; Afif Arahman; Fatma Nabila; Erra Fazira MT; Nabila Br Surbakti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the development, challenges, and implementation strategies of inclusive education in Indonesia. Inclusive education is a fundamental right that ensures all individuals, including those with special needs, have access to quality education without discrimination. Despite the existence of various national policies supporting inclusive education, significant barriers remain in practice, including limited resources, inadequate teacher training, and persistent social stigma towards children with special needs (CWSN). This literature review aims to identify the key challenges faced in the implementation of inclusive education and to propose effective strategies based on recent academic research. The findings reveal a gap between policy and practice, highlighting the need for comprehensive approaches that address both theoretical frameworks and practical solutions. The study contributes to the ongoing discourse on inclusive education by providing actionable recommendations for policymakers, educators, and stakeholders to enhance the quality and accessibility of education for all students in Indonesia.